Sistema bitcoin, lavagem de dinheiro e regulação - Telles, Christiana Mariani da Silva (2019)
The purpose of this dissertation is to study the Bitcoin System in order to investigate its use as an instrument for the practice of money laundering. The research is descriptive, aiming to provide an organized view of the subject to readers and regulators. The dissertation is divided into 5 (five) chapters at the end of which it is intended to contribute to the conception of a more effective regulatory environment. Chapter 2 demonstrates what bitcoins are and how Bitcoin System and Blockchain works. Chapter 3 briefly discusses the legal nature of bitcoins. Chapter 4 examines the crime of money laundering, investigating how the Bitcoin System is used to practice the crime in question. Chapter 5 examines the measures taken by Brazil, the United States, Europe, and the international community to prevent the practice of money laundering. Chapter 6 discusses whether the current regulation is adequate to prevent the practice of the crime in question, identifying elements capable of contributing to the improvement of regulation and discussing whether traditional regulatory models are able to cope with the challenges generated by new technologies. It is said that such challenges demand, in addition to the search for traditional regulatory responses, that could be refined, the adoption of unprecedented ways of approaching and thinking about the problem, taking into account the new elements brought by cryptocurrencies. It is also questioned whether the lack of specific regulations for cryptocurrencies is related to the expansion of criminal activities and observed that there is still no reliable data on the use of bitcoins for the practice of money-laundering crime, and that the volumes operated both legally and illegally are not significant. It is concluded that the present approach of the regulators is satisfactory, as long as it does not postpone the search for new ways of facing the problem. Finally, it is emphasized that the deepening of the discussions about the regulation of the Bitcoin System will depend on the ability of bitcoins to become a medium of exchange of generalized acceptance, adding that even if the Bitcoin System does not subsist it is important to register that it can leave marks, such as the creation of a global payment system that is no longer based on trust deposited in governments or financial intermediaries, but on algorithms and encryption .